Protein import into isolated pea root leucoplasts - Chu, Chiung-Chih; Li, Hsou-min (Frontiers in Plant Science, 2015)
Leucoplasts are important organelles for the synthesis and storage of starch, lipids and proteins. However, molecular mechanism of protein import into leucoplasts and how it differs from that of import into chloroplasts remain unknown. We used pea seedlings for both chloroplast and leucoplast isolations to compare within the same species. We further optimized the isolation and import conditions to improve import efficiency and to permit a quantitative comparison between the two plastid types. The authenticity of the import was verified using a mitochondrial precursor protein. Our results show that, when normalized to Toc75, most translocon proteins are less abundant in leucoplasts than in chloroplasts. A precursor shown to prefer the receptor Toc132 indeed had relatively more similar import efficiencies between chloroplasts and leucoplasts compared to precursors that preferred Toc159. Furthermore we found two precursors that exhibited very high import efficiency into leucoplasts. Their transit peptides may be candidates for delivering transgenic proteins into leucoplasts and for analyzing motifs important for leucoplast import.